1996
DOI: 10.1007/s004310050527
|View full text |Cite
|
Sign up to set email alerts
|

The use of acoustic reflectometry in the study of middle ear effusion in children suffering from acute otits media, upper respiratory tract infection and in healthy children

Abstract: Middle ear effusion is not generally a particularly significant clinical problem in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

1997
1997
1998
1998

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Last year colleagues and I reported another study on the occurrence and importance of middle ear effusion 4. With careful clinical observation and follow up, and using acoustic reflectometry as an objective measurement, we found that middle ear effusion is common.…”
mentioning
confidence: 69%
“…Last year colleagues and I reported another study on the occurrence and importance of middle ear effusion 4. With careful clinical observation and follow up, and using acoustic reflectometry as an objective measurement, we found that middle ear effusion is common.…”
mentioning
confidence: 69%
“…Bollag et al found 36% of slightly older children to have MEE by using acoustic re¯ectometry in Switzerland (Table 1) [1]. Unfortunately, it is not possible to ®nd out how many of these children were earlier undiagnosed in these studies.…”
Section: Discussionmentioning
confidence: 93%
“…chronic suppurative otitis media with or without cholesteatoma) and to prevent impaired hearing caused by middle ear effusion. A more conservative approach with watchful waiting has been chosen in some other countries [4,5]. Although recurrent acute otitis media does not seem to cause any permanent hearing loss [9] and there is no overall consensus that middle ear effusion would have long-term effects on language and learning [2], the acute complications and chronic suppurative otitis media and cholesteatoma [10] have become rare in our country concurrently with the use of this active strategy.…”
Section: Discussionmentioning
confidence: 99%
“…inflammtion of the tympanic membrane with a relatively normal mobility, is usually present in the early stages of acute otitis media, and some authors regard it as part of acute otitis media [3,5]. We think that although children with this type of finding may need surveillance, they should not be regarded as having acute otitis media, but mere acute upper respiratory tract infection, and that the finding of middle ear effusion should be an essential part of the diagnostic criteria for acute otitis media.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation